Water-soluble film and packaging

By adjusting the roughness and convex shape of the water-soluble film, the problem of uneven sealing strength in the prior art is solved, and excellent sealing strength uniformity under high-speed sealing conditions is achieved, and the overall performance of the packaging body is improved.

CN114008114BActive Publication Date: 2025-03-28KURARAY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080044802.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-17
Filing Date
2020-07-15
Publication Date
2025-03-28
Estimated Expiration
2040-07-15

AI Technical Summary

Technical Problem

In the prior art, when producing a packaging body with high-end and excellent glossy, it is difficult to achieve uniformity of sealing strength, especially under high-speed sealing conditions, seal defects and content leakage are prone to occur.

Method used

By adjusting the ratio of the average length of the roughness curve elements in the length direction and the width direction of the water-soluble film surface containing polyvinyl alcohol resin to 1.2 or more and 2.5 or less, combined with the convex shape with long sides in the length direction, the convex shape and roughness of the film surface are optimized to improve the uniformity of the sealing strength.

Benefits of technology

It achieves excellent sealing strength uniformity under high-speed sealing conditions, reduces the risk of packaging bag rupture and content leakage, and improves the overall performance of the packaging body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114008114B_ABST
    Figure CN114008114B_ABST
Patent Text Reader

Abstract

The present invention provides a water-soluble film suitable for manufacturing a packaging body having excellent uniformity of sealing strength and excellent uniformity of sealing strength when sealed at high speed, and a packaging body using the same. A water-soluble film comprising a polyvinyl alcohol resin, wherein the ratio RSm (LD / TD) of the average length RSm (LD) of the roughness curve element in the longitudinal direction of at least one side of the film surface to the average length RSm (TD) of the roughness curve element in the width direction is 1.2 or more and 2.5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-soluble film containing a polyvinyl alcohol resin which is suitable for packaging of various medicines and the like, and a packaging body using the same. Background Art

[0002] Conventionally, water-soluble films have been used in a wide range of fields, such as packaging of various chemicals such as liquid detergents, pesticides, and fungicides, and seed tapes containing seeds, by utilizing their excellent solubility in water.

[0003] Polyvinyl alcohol resin (hereinafter sometimes referred to as "PVA") is mainly used as a water-soluble film for this purpose. In addition, a concavo-convex shape is sometimes provided on the film surface for the purpose of improving matte or smoothness of the films. Methods for providing the concavo-convex shape include a method of molding a film-forming stock solution containing a filler in a PVA aqueous solution and a method of embossing the produced film (for example, Patent Document 1).

[0004] Patent Document 2 describes that, in the production of a drug package, when laminating a water-soluble film, by laminating embossed surfaces or non-embossed surfaces together, a drug package having excellent appearance characteristics can be obtained.

[0005] Previous technical literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2017-119434

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2017-110213 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] In recent years, from the perspective of appearance design, there has been an increasing demand for packaging bodies with a glossy and high-grade feel. In this case, a packaging body is produced in which surfaces with larger irregularities, such as an embossed surface, are bonded to each other and the surface with smaller irregularities becomes the surface side. On the other hand, in order to improve productivity, it is sometimes required to increase the manufacturing speed of the packaging bag and seal it at a high speed. However, if the sealing is performed at a high speed, the water applied as a paste is not applied evenly, or the air is not fully discharged from the packaging body to the outside and remains in the sealed part, and remains as a sealing defect, so that the sealing strength is likely to become uneven. As a result, there is a situation where the packaging bag breaks from the part with weak sealing strength and the contents leak out.

[0011] An object of the present invention is to provide a water-soluble film which can be suitably used for manufacturing a package having excellent uniformity of seal strength and which has excellent uniformity of seal strength when sealed at high speed, and a package using the same.

[0012] Means for solving technical problems

[0013] As a result of in-depth research, the present inventors focused on the linear roughness in the length direction and the linear roughness in the width direction of the surface of a water-soluble film containing a polyvinyl alcohol resin, and found that the above-mentioned problem can be solved by setting the ratio of the average lengths of the roughness curve elements in the length direction and the width direction to a specific range. Based on this finding, the present invention was completed through further research.

[0014] That is, the present invention relates to the following:

[0015] [1] A water-soluble film comprising a polyvinyl alcohol resin, wherein:

[0016] The ratio RSm (LD / TD) of the average length RSm (LD) of the roughness curve elements in the longitudinal direction of at least one film surface to the average length RSm (TD) of the roughness curve elements in the width direction is 1.2 or more and 2.5 or less.

[0017] Furthermore, the present invention relates to the following:

[0018] [2] The water-soluble film according to [1], wherein the film surface has a plurality of convex shapes having long sides in the longitudinal direction,

[0019] [3] The water-soluble film according to [2], wherein the average aspect ratio of the convex shape is 2 or more and 10 or less,

[0020] [4] The water-soluble film according to [2] or [3], wherein the average height of the convex shape is 0.5 μm or more and 5 μm or less,

[0021] [5] The water-soluble film according to any one of [2] to [4], wherein the average width of the convex shape is 10 μm to 50 μm, and the average length is 30 μm to 100 μm.

[0022] [6] The water-soluble film according to any one of [2] to [5], wherein the shape of the protrusion is a shape provided by transfer during molding,

[0023] [7] The water-soluble film according to any one of [2] to [6], wherein the convex portion has a shape provided by embossing.

[0024] [8] The water-soluble film according to any one of [1] to [7], wherein the ratio Ra (M / G) of the arithmetic mean roughness Ra of the film surface between the front side and the back side is 2 or more and 10 or less,

[0025] [9] The water-soluble film according to any one of [1] to [8], wherein the film surface having RSm (LD / TD) of 1.2 or more and 2.5 or less is a matte surface.

[0026] Furthermore, the present invention relates to the following contents:

[0027]

[10] A package, wherein the water-soluble film according to any one of [1] to [9] contains a drug,

[0028]

[11] The packaging body according to

[10] , wherein the glossy surface is an outer surface, and

[0029]

[12] According to the package described in

[10] or

[11] , the drug is a pesticide, a detergent or a fungicide.

[0030] Effects of the Invention

[0031] According to the present invention, there are provided a water-soluble film which can be suitably used for production of a package having excellent uniformity of seal strength and which has excellent uniformity of seal strength when sealed at high speed, and a package using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram of an example of the shape of the convex portions on the surface of the water-soluble film of the present invention.

[0033] Figure 2 This is a schematic diagram of another example of the shape of the convex portions on the surface of the water-soluble film of the present invention. DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will be described in detail.

[0035] The water-soluble film of the present invention contains polyvinyl alcohol resin (PVA). Moreover, the water-soluble film of the present invention is a water-soluble film, that is, the ratio RSm(LD) / RSm(TD) (hereinafter, sometimes referred to as RSm(LD / TD)) of the average length RSm(LD) of the roughness curve element in the length direction of at least one side of the film surface to the average length RSm(TD) of the roughness curve element in the width direction is 1.2 or more and 2.5 or less. Here, the length direction of the film surface is the main orientation direction of the PVA molecules in the film. And, the direction parallel to the film surface and perpendicular to the length direction is set as the width direction.

[0036] <Surface roughness of film>

[0037] In the present invention, as an index representing the surface roughness of the film, the average length RSm of the roughness curve element obtained by measuring the roughness of the film surface with a laser confocal microscope (e.g., "OLS3100" manufactured by Olympus Corporation) is used. Unlike conventional optical microscopes, a laser confocal microscope uses a laser beam with a specific wavelength and excellent straightness, and detects only the light focused on the sample surface through an objective lens. In this optical system, the reflected light from outside the focus is almost cut off, and only the information of the focus position is obtained. The laser confocal microscope has a resolution in the direction of the optical axis (the direction of the sample thickness), so it is possible to perform three-dimensional measurements of surface concave-convex shapes, etc. The average length RSm of the roughness curve element is one of the parameters of the line roughness obtained by measuring the roughness of the solid surface shown in JIS B 0601-2001.

[0038] When the above-mentioned laser confocal microscope is used to measure the average length RSm of the roughness curve elements in the length direction and the width direction of the surface of the water-soluble film, the RSm (LD / TD) of at least one side of the film surface of the water-soluble film of the present invention is in the range of more than 1.2 and less than 2.5. With RSm (LD / TD) in the above range, the uniformity of the sealing strength of the obtained film is excellent. This means that the average length of the peaks or valleys constituting the contour elements in the length direction is greater than the average length of the peaks or valleys constituting the contour elements in the width direction, that is, the peaks or valleys on the film surface become longer in the length direction. Thus, it is believed that when a paste is applied on the film surface, the applied paste is easy to flow in the length direction, so the paste is evenly applied, and as a result, the uniformity of the sealing strength is improved. RSm (LD / TD) is preferably more than 1.4. From the perspective of productivity, RSm (LD / TD) is preferably less than 2.0.

[0039] From the perspective of uniformity of sealing strength, the average length RSm (LD) of the roughness curve element in the length direction is preferably 10 μm or more and 30 μm or less. On the other hand, from the perspective of sealing strength, the average length RSm (TD) of the roughness curve element in the width direction is preferably 5 μm or more and 20 μm or less, and more preferably 5 μm or more and 15 μm or less.

[0040] When the arithmetic mean roughness Ra of the two surfaces of the film is measured respectively using the same laser confocal microscope as described above, the ratio of the arithmetic mean roughness Ra of the two surfaces, that is, the front-to-back ratio of the arithmetic mean roughness Ra (hereinafter, sometimes referred to as Ra(M / G)) is preferably greater than 2 and less than 10. When Ra(M / G) is within the above range, it is easy to take into account both the uniformity of the sealing strength when sealing at high speed and the good appearance of the obtained packaging bag. Ra(M / G) is preferably greater than 3 and less than 7. In addition, when the Ra of both sides of the film is measured, when the side with smaller Ra is set as the glossy side and the larger side is set as the matte side, the Ra of the matte side (Ra(M)) is divided by the Ra of the glossy side (Ra(G)) to obtain the front-to-back ratio Ra(M / G) of the arithmetic mean roughness Ra of the film surface. For either the matte side or the glossy side, the arithmetic mean roughness Ra of the surface of the water-soluble film in the length direction and the width direction is measured respectively, and the average value thereof is set as the arithmetic mean roughness Ra of the film surface. Ra(G) is preferably 0.5 μm or less, and more preferably 0.4 μm or less. When Ra(G) is within the above range, the glossiness of the obtained packaging bag is excellent. In addition, it is preferred that Rsm(LD / TD) of the matte surface satisfies the above range.

[0041] <Surface shape of film>

[0042] The water-soluble film of the present invention preferably has a plurality of convex shapes having long sides in the longitudinal direction on at least one side of the film surface. When the film surface has convex shapes oriented in the longitudinal direction, when the paste is applied to the film surface, the applied paste easily flows in the longitudinal direction, so the paste is evenly applied, thereby more easily obtaining the effect of the present invention that the uniformity of the sealing strength is improved. The convex shape may be roughly rectangular or roughly elliptical.

[0043] The surface shape and surface roughness of the film can also be observed using a laser confocal microscope. Figure 1 As shown in the schematic diagram of , when the convex shape is roughly rectangular, the long side is set as the length and the short side is set as the width. The average of the length and width of any 100 convex shapes is set as the average length and average width, respectively. Figure 1 As shown in the figure, the distance from the flat part around the convex shape to the maximum height position of the convex shape is set as the height, and the average of the heights of any 100 convex shapes is set as the average height. In addition, the distance in the width direction of two adjacent convex shapes is called the interval, and the average of the intervals of any 100 adjacent groups of convex shapes is set as the average interval.

[0044] Figure 1 The case where the convex portion is substantially rectangular is shown, but Figure 2As shown in the schematic diagram, the same also applies to the case where the convex shape is roughly elliptical. When the convex shape is roughly elliptical, the major axis is set as the length and the minor axis is set as the width. The average length and the average width are the same as when the convex shape is roughly rectangular. When the convex shape is roughly elliptical, the distance from the flat part around the convex shape to the maximum height position of the convex shape is also set as the height, and the average of the heights of any 100 convex shapes is set as the average height. In addition, the shortest distance in the width direction of the major axes of two adjacent convex shapes is subtracted from the distance of their respective minor axes (in Figure 2 The interval is set to a value half the sum of the lengths of the minor axis A and the minor axis B, and the average of the intervals of any 100 adjacent groups of convex shapes is set to an average interval.

[0045] When the protrusion is roughly rectangular, Figure 1 As shown, the preferred length is parallel to the length direction of the film. When the convex shape is substantially elliptical, the preferred major axis is parallel to the length direction of the film. Furthermore, the convex shapes are preferably parallel to each other. In addition, when the convex shapes are not parallel to each other, the widths of the two adjacent convex shapes are set to the value of the shortest distance.

[0046] The average width of the convex shape is preferably 10 μm or more and 50 μm or less. If the average width is within this range, the independence of the convex portion is excellent, and it will not be pressed or bent during sealing, so that the effect of the convex portion is fully exerted. In addition, the area occupied by the convex portion on the film surface becomes appropriate, so as to fully exert the effect of the convex portion. The average width is more preferably 15 μm or more and 30 μm or less.

[0047] The average length of the convex shape is preferably 30 μm to 100 μm. When the average length is within the above range, the average aspect ratio of the convex shape described below is within an appropriate range, thereby improving the uniformity of the sealing strength. The average length is more preferably 40 μm to 80 μm.

[0048] The average aspect ratio of the convex shape is preferably greater than 2 and less than 10. Here, the average aspect ratio is a value obtained by dividing the average length of the convex shape by the average width. If the average aspect ratio is within this range, the lateral escape of the paste when sealing along the length direction is suppressed, thereby easily ensuring the uniformity of the sealing strength. In addition, when sealing, the escape path of air is ensured and the sealing defects are reduced, thereby easily ensuring the uniformity of the sealing strength.

[0049] The average height of the convex shape is preferably 0.5 μm or more and 5 μm or less. If the average height is too small, the effect as a convex portion cannot be fully exerted. On the other hand, if the average height is too large, there is a possibility that the water solubility may be uneven due to the difference in film thickness in the film. The average height is more preferably 1 μm or more and 4 μm or less.

[0050] The average interval (average pitch) between the convex shapes is preferably 10 μm or more and 30 μm or less. If the average interval is within this range, it is easy to ensure an escape path for the applied paste and to suppress the accumulation of air in the sealing direction.

[0051] In the present invention, the focus is on controlling the above RSm (LD / TD) within the above range. As the control method, for example, there can be cited a method for adjusting the type of polyvinyl alcohol resin (saponification degree, modification amount, mixing ratio of unmodified PVA / modified PVA, etc.), a method for adjusting the amount of plasticizer added, a method for adding an organic or inorganic filler, a method for adjusting film manufacturing conditions (surface temperature of the support, heat treatment conditions, drawing conditions, etc.), a method for adjusting the concavo-convex shape of the support surface, a method for adjusting embossing processing conditions (film moisture content, processing temperature, processing pressure, processing time, etc.), or a method for adjusting by a combination thereof. Among these methods, the method of adjusting the concavo-convex shape of the support surface and the method of adjusting the embossing processing conditions are easy to control the concavo-convex shape of the film surface, and are therefore preferred.

[0052] <Polyvinyl alcohol resin>

[0053] The water-soluble film of the present invention contains a polyvinyl alcohol resin (PVA).

[0054] As PVA, a polymer produced by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester monomer can be used.

[0055] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl 2,2-dimethylpropionate, and vinyl versatate. Among them, the vinyl ester monomer is preferably vinyl acetate.

[0056] The vinyl ester polymer is preferably a polymer obtained by using only one or two or more vinyl ester monomers as a monomer, and more preferably a polymer obtained by using only one vinyl ester monomer as a monomer. In addition, the vinyl ester polymer may be a copolymer of one or two or more vinyl ester monomers and other monomers copolymerizable therewith.

[0057] Examples of other monomers include ethylene; olefins having 3 to 30 carbon atoms such as propylene, 1-butene, and isobutylene; acrylic acid or its salts; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or its salts; methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide, N-methyl-2-acrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidepropanesulfonic acid or its salts, dimethylaminopropylacrylamide or its salts, N-hydroxymethylacrylamide or acrylamide derivatives such as those derived from the same; methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid or its salts, dimethylaminopropylmethacrylamide or its salts, N-hydroxymethylmethacrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, and N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, vinyl ethyl ether, n-propyl vinyl ether, isopropyl vinyl ether, vinyl n-butyl ether, vinyl isobutyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, and octadecyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; propylene compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters, or anhydrides; itaconic acid or its salts, esters, or anhydrides; vinyl silyl compounds such as vinyltrimethoxysilane; isopropenyl acetate, etc.

[0058] In addition, the vinyl ester polymer may have structural units derived from one or two or more of these other monomers.

[0059] From the viewpoint of improving the sealing property and mechanical strength of the water-soluble film, the proportion of the structural units derived from other monomers in the vinyl ester polymer (hereinafter, sometimes referred to as "modification degree") is preferably 15 mol% or less, and more preferably 5 mol% or less, based on the molar number of all structural units constituting the vinyl ester polymer. If the proportion of the structural units derived from other monomers is too much, it is sometimes difficult to adjust the concavo-convex shape of the film surface.

[0060] The degree of polymerization of PVA is not particularly limited, but is preferably in the following range. That is, from the viewpoint of ensuring sufficient mechanical strength of the water-soluble film, the lower limit of the degree of polymerization is preferably 200 or more, more preferably 300 or more, and further preferably 500 or more. On the other hand, from the viewpoint of improving the productivity of PVA or the productivity of the water-soluble film, the degree of polymerization is preferably 8,000 or less, more preferably 5,000 or less, and further preferably 3,000 or less.

[0061] Here, the degree of polymerization means the average degree of polymerization measured in accordance with JIS K 6726-1994. That is, in this specification, the degree of polymerization is determined by the following formula based on the limiting viscosity [η] (unit: deciliter / g) measured in water at 30°C after saponification and purification of residual acetate groups in PVA.

[0062] Degree of polymerization Po = ([η] × 10 4 / 8.29) (1 / 0.62)

[0063] In the present invention, the value of deducting the above-mentioned degree of modification from the saponification degree of PVA is preferably 64 to 97 mol%. By adjusting this value within this range, the adjustment of the concavo-convex shape of the film surface becomes easy, and the sealing and mechanical strength of the water-soluble film can be taken into account. This value is more preferably 70 mol% or more, and more preferably 75 mol% or more. On the other hand, this value is more preferably 93 mol% or less, more preferably 91 mol% or less, and particularly preferably 90 mol% or less.

[0064] Here, the saponification degree of PVA refers to the ratio (mol %) of the molar number of vinyl alcohol units to the total molar number of structural units (typically vinyl ester monomer units) that can be converted into vinyl alcohol units by saponification and vinyl alcohol units.

[0065] The saponification degree of PVA can be measured in accordance with the description of JIS K 6726-1994.

[0066] The water-soluble film may contain a single type of PVA, or may contain two or more types of PVAs having different polymerization degrees, saponification degrees, modification degrees, etc.

[0067] The content of PVA in the water-soluble film is preferably 100% by mass or less. On the other hand, the content of PVA is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more.

[0068] <Plasticizer>

[0069] The water-soluble film preferably contains a plasticizer. By containing a plasticizer, the water-soluble film can be given the same softness as other plastic films. Therefore, the mechanical strength such as impact strength of the water-soluble film or the process passability during secondary processing becomes better.

[0070] As the plasticizer, for example, polyols such as ethylene glycol, glycerol, diglycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, and sorbitol can be cited. These plasticizers can be used alone or in combination of two or more. Among them, from the viewpoint of suppressing seepage to the surface of the water-soluble film, the plasticizer is preferably ethylene glycol or glycerol, and more preferably glycerol.

[0071] The content of the plasticizer in the water-soluble film is preferably more than 1 mass part, more preferably more than 3 mass parts, and more preferably more than 5 mass parts relative to PVA100 mass parts. On the other hand, the content of the plasticizer is preferably less than 70 mass parts, more preferably less than 50 mass parts, and more preferably less than 40 mass parts relative to PVA100 mass parts. If the content of the plasticizer is within the above range, the adjustment of the concavo-convex shape of the film surface becomes easy, and the improvement effect of mechanical properties such as the impact strength of the water-soluble film can be fully obtained. In addition, it is possible to appropriately prevent or suppress the excessive softening of the water-soluble film and the reduction in operability caused, or the problems such as oozing out to the surface.

[0072] <Starch / Water-soluble polymer>

[0073] The water-soluble film may contain water-soluble polymers other than starch and / or PVA. By containing water-soluble polymers other than starch and / or PVA, mechanical strength can be imparted to the water-soluble film, or the moisture resistance of the water-soluble film during operation can be maintained, or the speed of softening of the water-soluble film caused by absorption of water during dissolution can be adjusted.

[0074] Examples of starch include natural starches such as corn starch, potato starch, sweet potato starch, wheat starch, rice starch, tapioca starch, and sago starch; and processed starches that have been subjected to etherification, esterification, oxidation, and the like. Processed starches are particularly preferred.

[0075] The content of starch in the water-soluble film is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of PVA. When the content of starch is within the above range, the process passability of the water-soluble film can be prevented or suppressed from being deteriorated.

[0076] Examples of water-soluble polymers other than PVA include dextrin, gelatin, glue, casein, shellac, gum arabic, polyacrylamide, sodium polyacrylate, polyvinyl methyl ether, a copolymer of methyl vinyl ether and maleic anhydride, a copolymer of vinyl acetate and itaconic acid, polyvinyl pyrrolidone, cellulose, acetyl cellulose, acetyl butyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, sodium alginate, and the like.

[0077] The content of the water-soluble polymer other than PVA in the water-soluble film is preferably 15 parts by mass or less, more preferably 10 parts by mass or less relative to 100 parts by mass of PVA. If the content of the water-soluble polymer other than PVA is within the above range, the adjustment of the concavo-convex shape of the film surface becomes easy, and the water solubility of the water-soluble film can be fully improved.

[0078] <Surfactant>

[0079] The water-soluble film preferably contains a surfactant. By containing a surfactant, the handleability of the water-soluble film and the peelability of the water-soluble film from a molding device during production can be improved.

[0080] The surfactant is not particularly limited, and for example, anionic surfactants, nonionic surfactants, and the like can be used.

[0081] Examples of the anionic surfactant include carboxylic acid-based surfactants such as potassium laurate; sulfate-based surfactants such as octyl sulfate; and sulfonic acid-based surfactants such as dodecylbenzenesulfonate.

[0082] Examples of the nonionic surfactant include alkyl ether surfactants such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether; alkyl phenyl ether surfactants such as polyoxyethylene octylphenyl ether; alkyl ester surfactants such as polyoxyethylene laurate; alkylamine surfactants such as polyethylene glycol lauramide; alkylamide surfactants such as polyoxyethylene lauric acid amide; polypropylene glycol surfactants such as polyoxyethylene polyoxypropanolamine ether; alkanolamide surfactants such as lauramide diethanol and oleoyl diethanolamine; and propenyl phenyl ether surfactants such as polyoxyalkylene propenyl phenyl ether.

[0083] Such surfactants may be used alone or in combination of two or more. Among them, from the viewpoint of excellent effect of reducing surface abnormalities such as streaky defects when manufacturing water-soluble films, the surfactant is preferably a nonionic surfactant, more preferably an alkanolamide surfactant, and further preferably a dialkanolamide (e.g., diethanolamine, etc.) of an aliphatic carboxylic acid (e.g., a saturated or unsaturated aliphatic carboxylic acid having 8 to 30 carbon atoms, etc.).

[0084] The content of the surfactant in the water-soluble film is preferably more than 0.01 mass parts, more preferably more than 0.02 mass parts, and more preferably more than 0.05 mass parts relative to PVA100 mass parts. On the other hand, the content of the surfactant is preferably less than 10 mass parts, more preferably less than 1 mass part, more preferably less than 0.5 mass parts, and particularly preferably less than 0.3 mass parts relative to PVA100 mass parts. If the content of the surfactant is within the above range, the peelability of the water-soluble film during manufacture from the molding device becomes better, and it is difficult to cause the generation of agglomerations between the water-soluble films. In addition, it is also difficult to cause the problems such as the deterioration of the appearance of the water-soluble film caused by the oozing out of the surfactant to the surface of the water-soluble film or the agglomeration of the surfactant.

[0085] <Other ingredients>

[0086] The water-soluble film of the present invention may contain, in addition to plasticizers, starch, water-soluble polymers other than PVA, and surfactants, moisture, antioxidants, ultraviolet absorbers, lubricants, cross-linking agents, colorants, fillers, preservatives, mildewproofing agents, defoaming agents, other polymer compounds and other ingredients within the range that does not hinder the effects of the present invention.

[0087] The total mass of PVA, plasticizer, starch, water-soluble polymers other than PVA, and surfactant accounts for preferably 60 to 100% by mass, more preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass of the total mass of the water-soluble film.

[0088] <Water-soluble film>

[0089] There is no particular limitation on the total dissolution time of the water-soluble film of the present invention when immersed in deionized water at 10°C, but it is preferably in the following range. The total dissolution time is preferably within 300 seconds, and more preferably within 200 seconds. The water-soluble film whose upper limit of the total dissolution time is within the above range completes dissolution relatively early, and therefore can be suitable for use as a film for packaging (packaging material) of medicines, etc. On the other hand, the total dissolution time is preferably more than 5 seconds, more preferably more than 10 seconds, further preferably more than 15 seconds, and particularly preferably more than 20 seconds. In this way, if the water-soluble film has a not too short total dissolution time, it is difficult for the water-soluble film to have problems such as the generation of lumps between each other or a reduction in mechanical strength caused by the absorption of moisture in the atmosphere.

[0090] The total dissolution time when a water-soluble film is immersed in deionized water at 10° C. can be measured as follows.

[0091] <1> The water-soluble film is placed in a constant temperature and humidity chamber adjusted to 20°C-65%RH for 16 hours or more to adjust the humidity.

[0092] <2> After cutting out a rectangular sample of 40 mm in length and 35 mm in width from the humidified water-soluble film, fix it between two 50 mm × 50 mm plastic plates having a rectangular window of 35 mm in length and 23 mm in width, so that the length direction of the sample is parallel to the length direction of the window (hole) and the window is located approximately in the center of the width direction of the sample.

[0093] <3> 300 mL of deionized water was placed in a 500 mL beaker, and the mixture was stirred at 280 rpm using a magnetic stirrer equipped with a 3 cm long rod, while the water temperature was adjusted to 10°C.

[0094] <4> While being careful not to touch the bar of the magnetic stirrer, completely immerse the sample fixed to the plastic plate in <2> above in deionized water in a beaker.

[0095] <5> The time from immersion in deionized water to complete disappearance of the sample pieces dispersed in the deionized water as observed with the naked eye was measured.

[0096] The total dissolution time measured by the above method depends on the thickness of the sample. However, in the present specification, the total dissolution time is the time required for a sample of the above size to be completely dissolved, regardless of the thickness.

[0097] The thickness of the water-soluble film is not particularly limited, but is preferably in the following range. That is, the thickness is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 100 μm or less. On the other hand, the thickness is preferably 5 μm or more, more preferably 10 μm or more, further preferably 15 μm or more, and particularly preferably 20 μm or more. Since the thickness in the above range is not too large, the secondary processability of the water-soluble film can be appropriately prevented from being deteriorated. On the other hand, since it is not too small, sufficient mechanical strength can be ensured in the water-soluble film.

[0098] Alternatively, the thickness of the water-soluble film may be measured at any 10 locations (for example, any 10 locations on a straight line drawn along the longitudinal direction of the water-soluble film), and their average value may be determined as the thickness of the water-soluble film.

[0099] The glossiness of the water-soluble film is not particularly limited, but from the viewpoint of appearance design, when glossiness is required, the glossiness of the glossy surface is preferably in the following range. That is, the glossiness of the glossy surface is preferably 30 or more, more preferably 40 or more, and further preferably 50 or more. If the glossiness of the glossy surface is within the above range, when two water-soluble films are bonded together so that the glossy surface becomes the outer surface to produce a packaging body, the obtained packaging bag has excellent glossiness.

[0100] <Method for producing water-soluble film>

[0101] The method for producing the water-soluble film of the present invention is not particularly limited, and for example, the following method can be used.

[0102] Examples include a casting molding method, a wet molding method (discharging into a poor solvent), a dry-wet molding method, a gel molding method (a method of temporarily cooling and gelling the molding stock solution and then extracting and removing the solvent) or a combination thereof to mold a uniform molding stock solution obtained by adding a solvent, an additive, etc. to PVA; a melt extrusion molding method or an inflation molding method in which a molding stock solution obtained by using an extruder or the like is extruded from a T-die or the like to perform molding. Among them, as a method for producing a water-soluble film, a casting molding method and a melt extrusion molding method are preferred. If these methods are used, a homogeneous water-soluble film can be obtained with high productivity.

[0103] Hereinafter, a method for producing a water-soluble film using a casting molding method or a melt extrusion molding method will be described.

[0104] First, prepare a molding stock solution containing PVA, a solvent, and, if necessary, additives such as a plasticizer. When the molding stock solution contains an additive, the ratio of the additive in the molding stock solution to PVA is substantially equal to the ratio of the additive in the water-soluble film obtained above to PVA.

[0105] Next, the molding stock solution is drooled (supplied) onto the support in a film-like manner. Thus, a liquid film of the molding stock solution is formed on the support. The support may be made of a polymer (e.g., polyethylene terephthalate (PET), polyethylene naphthalate (PEN), acetyl cellulose, polycarbonate, paper, resin-laminated paper, etc.) or a metal (e.g., iron, copper, aluminum, etc.).

[0106] The liquid coating is dried on the support to remove the solvent, thereby solidifying and becoming a thin film. The drying can be accelerated by heating. The solidified film can be peeled off from the support, further dried by a drying roller, a drying oven, etc. as needed, and heat treated as needed. The molding is carried out intermittently, semi-intermittently or continuously. The storage method of the film is not particularly limited, and it can be wound in a roll or overlapped (cut in advance).

[0107] The volatility of the molding stock solution (the concentration of volatile components such as solvents removed by volatilization or evaporation during molding) is preferably 50 to 90% by mass, and more preferably 55 to 80% by mass. If the volatility is within the above range, the viscosity of the molding stock solution can be adjusted within an appropriate range, so the moldability of the water-soluble film (liquid coating) is improved, and a water-soluble film with a uniform thickness can be easily obtained.

[0108] Here, the "volatile content of the molding stock solution" in this specification refers to a value obtained by the following formula.

[0109] Volatile content of film-forming stock solution (mass %) = {(Wa-Wb) / Wa}×100

[0110] In the formula, Wa represents the mass (g) of the film-forming stock solution, and Wb represents the mass (g) of the film-forming stock solution after drying Wa (g) in an electric drying machine at 105°C for 16 hours.

[0111] There are no particular restrictions on the method for adjusting the molding stock solution. Examples include a method of dissolving PVA and additives such as plasticizers and surfactants in a dissolving tank or the like; a method of melt-kneading the aqueous PVA with additives such as plasticizers and surfactants using a single-axis or double-axis extruder; and the like.

[0112] As one embodiment, the surface temperature of the support body on which the molding stock solution is drooled is preferably 50 to 110° C., more preferably 60 to 100° C., and even more preferably 65 to 95° C. If the surface temperature is within the above range, the liquid coating can be dried at a high efficiency rate, and thus the time required for drying the liquid coating will not be excessively prolonged, and the productivity of the water-soluble film will not be reduced. In addition, by drying the liquid coating at such a speed, abnormalities such as foaming are less likely to occur on the surface of the water-soluble film.

[0113] While heating the liquid coating on the support, hot air at a wind speed of 1 to 10 m / s can be evenly blown to the entire area of ​​the non-contact surface side of the liquid coating. In this way, the drying speed of the liquid coating can be adjusted. The temperature of the hot air blown to the non-contact surface side is preferably 50 to 150°C, more preferably 70 to 120°C. If the temperature of the hot air is within the above range, the drying efficiency or drying uniformity of the liquid coating can be further improved.

[0114] The water-soluble film is preferably dried (solvent removed) on the support to a volatile content of 5 to 50% by mass, then peeled off from the support and further dried as needed. In another embodiment, the film can be completely or substantially dried on the support and then stored in a state where it is placed on the support for subsequent steps.

[0115] The drying method is not particularly limited, and examples thereof include a method of passing through a drying furnace and a method of contacting with a drying roll.

[0116] When a plurality of drying rollers are used to dry the water-soluble film, it is preferred that one side and the other side of the water-soluble film are contacted with the drying rollers alternately. In this way, the crystallinity of the PVA on both sides of the water-soluble film can be made uniform. In this case, the number of drying rollers is preferably 3 or more, more preferably 4 or more, and further preferably 5 to 30.

[0117] The temperature of the drying furnace or the drying roller is preferably 40 to 110° C. The upper limit of the temperature of the drying furnace or the drying roller is more preferably 100° C. or less, further preferably 90° C. or less, and particularly preferably 85° C. or less. On the other hand, the lower limit of the temperature of the drying furnace or the drying roller is more preferably 45° C. or more, further preferably 50° C. or more.

[0118] The dried water-soluble film may be further heat-treated as needed. The mechanical strength, water solubility, birefringence and other properties of the water-soluble film may be adjusted by heat treatment. The heat treatment temperature is preferably 60 to 135° C. The upper limit of the heat treatment temperature is more preferably 130° C. or less.

[0119] In order to make the surface of the water-soluble film have the desired surface roughness, a method of obtaining a water-soluble film with a concave-convex shape by transferring during molding by applying concave-convex to the surface of the support or a method of applying a concave-convex shape to the water-soluble film by embossing can be adopted. For example, by forming a concave portion with RSm (LD / TD) of 1.2 or more and 2.5 or less on the surface of the support, a water-soluble film with a target surface roughness can be obtained. In addition, by forming a concave portion having long sides in the length direction on the surface of the support, a water-soluble film having a convex shape having long sides in the length direction can be obtained. The method of obtaining a water-soluble film with a concave-convex shape when molding by applying concave-convex to the surface of the support is easy to obtain a water-soluble film composed of a matte surface with a desired RSm (LD / TD) and a glossy surface with an appropriate Ra, and can take into account the uniformity of the sealing strength during high-speed sealing and a good appearance, so it is preferred.

[0120] When the water-soluble film having a concavo-convex shape is obtained by transferring the concavo-convex shape to the support surface during molding, the film is dried at a temperature of preferably 50 to 170° C., more preferably 60 to 140° C. The drying time on the support is preferably 0.5 to 20 minutes, more preferably 1 to 15 minutes.

[0121] When the water-soluble film is embossed to give a concavo-convex shape, the processing temperature is preferably 60 to 150° C., more preferably 80 to 140° C. The processing pressure is preferably 0.1 to 15 MPa, more preferably 0.3 to 8 MPa. The film conveying speed during embossing is preferably 5 m / min or more, more preferably 10 to 30 m / min.

[0122] The water-soluble film thus produced is further subjected to humidity conditioning treatment, cutting of both ends (ears) of the film, etc. as required, and then wound around a cylindrical core in a roll shape and moisture-proof packaging to obtain a product. In another embodiment, the film is cut into uniform sizes and overlapped with a release film inserted as required, and moisture-proof packaging is performed to obtain a product.

[0123] <Application>

[0124] The water-soluble film (water-soluble film) of the present invention can be more suitably used in various film applications to which conventional water-soluble films are applicable.

[0125] Examples of the film applications include films for drug packaging, base films for hydraulic transfer, base films for embroidery, release films for artificial marble molding, seed packaging films, and films for waste collection bags. Among them, the water-soluble film of the present invention is preferably suitable for use as a film for drug packaging.

[0126] When the water-soluble film of the present invention is applied to a film for packaging pharmaceutical agents, examples of the pharmaceutical agents include agricultural chemicals, detergents (including bleaching agents), fungicides, and edibles.

[0127] The physical properties of the drug are not particularly limited, and it may be acidic, neutral, or alkaline.

[0128] Furthermore, the agent may contain a boron-containing compound or a halogen-containing compound.

[0129] The medicine may be in the form of powder, block, gel or liquid.

[0130] The packaging method is not particularly limited, but from the viewpoint of handling, a unit packaging method in which the drug is packaged (preferably sealed) in unit amounts is preferred.

[0131] The package of the present invention can be obtained by applying the water-soluble film of the present invention to a film for packaging medicines to package medicines. In other words, the package of the present invention includes a packaging material (capsule) composed of the water-soluble film of the present invention and a medicine contained in the packaging material.

[0132] By laminating the water-soluble film of the present invention and the surfaces having desired surface roughness to each other or laminating the surface having desired surface roughness to the other side surface to produce a package body, a package body having excellent uniformity of sealing strength can be obtained.

[0133] There is no particular limitation on the method of laminating the films, and a known method can be used, such as a sealing method of heating and pressing the overlapping films, a method of applying a paste to the sealing surface and then pressing it, and a combination thereof. Among these methods, a method of applying a paste to the sealing surface and then pressing it without a heating device is preferred. In the case of a water-soluble film containing PVA, examples of the paste include a PVA aqueous solution, a boric acid aqueous solution, and water. From the perspective of operability, water-based sealing is more preferred.

[0134] Example

[0135] Hereinafter, the present invention will be specifically described by way of examples, etc., but the present invention is not limited to the following examples in any way. In addition, the evaluation items and methods used in the following examples and comparative examples are as follows.

[0136] (1) Average length RSm and arithmetic mean roughness Ra of the roughness curve element of the film surface

[0137] The water-soluble film was fixed on a glass slide, and the surface roughness was analyzed by a laser microscope. From the 20x measurement image, the surface roughness was measured on an arbitrary straight line within the range of about 560μm in the length direction (LD) of the film and about 430μm in the width direction (molding width direction, TD), and the RSm(LD) and RSm(TD) as well as Ra(LD) and Ra(TD) on the measured straight line were automatically calculated in the device. The measurement position was changed, 10 positions were measured on each straight line, and the average value was set as the analysis value. The average value of Ra(LD) and Ra(TD) was set as Ra of the film surface, the Ra of the matte surface was set as Ra(M), and the Ra of the glossy surface was set as Ra(G). The detailed measurement conditions and calculation conditions are as follows.

[0138] Measuring device: OLS3100 (manufactured by Olympus Corporation)

[0139] Measurement conditions: Manual measurement, pitch…0.30, step length…about 80 to 150 (adjusted appropriately according to the sample)

[0140] Identification of minimum height: Section curve…10% of Pz, Roughness curve…10% of Rz, Fluctuation curve…10% of Wz

[0141] Minimum length recognition: 1% of the reference length (field of view)

[0142] Cross-section height difference calculation object load length ratio: Rmr1…30%, Rmr2…60%

[0143] (2) Observation of film surface shape

[0144] Under the same conditions as in (1) above, 20-fold measurement images were obtained for each of the five film samples. The entire area of ​​the measurement field of view of each unit image obtained, which was approximately 430 μm × approximately 560 μm, was set as the observation range, and 20 convex portions, a total of 100 convex portions, were selected from each field of view, and their shapes were measured using the length measurement and height measurement software in the analysis software attached to the measurement device (OLS3100).

[0145] (3) Glossiness

[0146] The water-soluble film was cut into a square sample with a length direction (LD) of about 5 cm and a width direction (TD) of about 5 cm, and kept in an environment of 23°C-35% RH for more than 16 hours for humidity control. The glossiness of the glossy surface of the sample after humidity control was measured at an angle of 60° in the LD and TD directions using a gloss meter in accordance with JIS Z 8741-1997, and the average value was set as the glossiness.

[0147] (4) Sealing strength

[0148] The matte surfaces of the water-soluble films were bonded to each other in a water-tight manner, and the seal strength and unevenness were measured.

[0149] Six rectangular samples with a length direction (LD) of about 30 cm and a width direction (TD) of about 10 cm were cut out from the water-soluble film and kept in an environment of 23°C-35% RH for more than 16 hours to adjust the humidity. A sample that had been adjusted in the same environment was placed on a table, and the four corners of the film were fixed with tape. Furthermore, another sample was overlapped on it, and the two ends of the 10 cm side were fixed with tape, and the unfixed end was passed to the ESIPROOF proofing roller using a 140 / 10 anilox roller. 0.5 mL of deionized water was poured on the scraper of the ESIPROOF proofing roller, and the roller was pulled at a speed of about 7.5 cm / second to bond the two samples. In addition, at this time, the roller was not pulled to the end of the sample, leaving a portion that was not bonded to the end of the sample so that it could be set in the chuck of the tensile tester. Three long strip test pieces with a width of 25 mm with LD as the long side were cut out from the bonded sample. The above operation was repeated two more times to prepare 9 test pieces.

[0150] After 10 minutes from the bonding, the test piece was placed in a tensile testing machine and peeled at a tensile speed of 254 mm / min in accordance with the T-die peel test based on JIS K 6854-3: 1999. The average value of the 9 peel forces obtained was set as the sealing strength, and the coefficient of variation (the value of dividing the standard deviation by the average value) was set as an index of the uniformity of the sealing strength.

[0151] <Example 1>

[0152] A molding stock solution was prepared by mixing 100 parts by mass of PVA (saponification degree 88 mol %, viscosity average polymerization degree 1700) obtained by saponifying polyvinyl acetate, 25 parts by mass of glycerin as a plasticizer, 0.1 parts by mass of lauramide diethanol as a surfactant, and water. The volatile content of the molding stock solution was 68% by mass.

[0153] Next, a metal support having a plurality of concave portions with long sides in the longitudinal direction (winding direction, LD) was used, and the molding stock solution was discharged from the T-shaped mold in a film-like manner onto the metal support (surface temperature 85° C.), thereby forming a liquid coating on the metal support. The metal support used a support having a surface with roughly elliptical concave and convex shapes. On the metal support, the entire surface of the metal support that was not in contact with the liquid coating was dried by blowing hot air at 110° C. Thereby, a water-soluble film was obtained.

[0154] Next, the water-soluble film was peeled off from the metal support. The thickness of the obtained water-soluble film was 76 μm.

[0155] The surface roughness, glossiness, static friction coefficient and sealing strength of the obtained water-soluble film were measured. In addition, the total dissolution time of the obtained water-soluble film when immersed in deionized water at 10° C. was measured by the above method and the result was 195 seconds.

[0156] <Example 2>

[0157] The PVA used in the preparation of the molding stock solution was changed to a maleic acid monomethyl ester (MMM) modified PVA (saponification degree 90 mol%, polymerization degree 1700, MMM modification amount 5 mol%), and the amount of glycerol was changed to 45 parts by mass. A water-soluble film was obtained in the same manner as in Example 1. The surface roughness, surface shape, glossiness and sealing strength of the obtained water-soluble film were measured. The results are shown in Table 1. In addition, the total dissolution time of the obtained water-soluble film when immersed in deionized water at 10°C was measured by the above method, and the result was 97 seconds.

[0158] <Comparative Example 1>

[0159] As in Example 1, a molding stock solution was used, and the molding stock solution was discharged from the T-shaped mold in a film form onto the support, i.e., a metal roller (surface temperature 80°C), to form a liquid coating on the metal roller. On the metal roller, the entire surface of the metal roller that was not in contact with the liquid coating was blown with hot air at 85°C to dry it. Thus, a water-soluble film was obtained. Next, the water-soluble film was peeled off from the metal roller, and one side and the other side of the water-soluble film were alternately contacted with multiple drying rollers (surface temperature 75°C) to dry it. Next, an embossing roller and a rubber roller, i.e., a back-flush roller, having a pear skin pattern with a surface roughness (arithmetic mean roughness Ra) of 3μm on the side that was not in contact with the metal roller were used. Under the conditions of an embossing roller temperature of 120°C, a back-flush roller temperature of 50°C, and a linear pressure of 25kg / cm, the film was embossed while being pushed at a speed of 12m / min, and then it was wound on a cylindrical core in a roll. The thickness of the obtained water-soluble film was 76 μm.

[0160] The surface roughness, glossiness and water sealing strength of the obtained water-soluble film were measured. The results are shown in Table 1.

[0161] <Comparative Example 2>

[0162] A water-soluble film was obtained in the same manner as in Comparative Example 1 except that the molding stock solution used was changed to the same molding stock solution as in Example 2. The surface roughness, glossiness, and water sealing strength of the obtained water-soluble film were measured. The results are shown in Table 1.

[0163] [Table 1]

[0164] Example 1 Example 2 Comparative Example 1 Comparative Example 2 PVA Degree of Polymerization 1700 1700 1700 1700 modified No modification MMM△5 No modification MMM△5 Saponification degree [mol%] 88 90 88 90 Plasticizer amount [wt%] 25 45 25 45 Film thickness 76 76 76 76 Manufacturing method Transfer Transfer Embossing Embossing convex shape Roughly oval Roughly oval (Pear peel) (Pear peel) Average length [μm] 72.1 58.7 - - Average width [μm] 16.5 19.3 - - Average aspect ratio 4.4 3.0 - - Average height [μm] 3.4 3.2 - - Average spacing [μm] 18.1 15.6 - - Matt surface RSm(TD)[μm] 12.6 11.5 54.8 25.8 RSm(LD)[μm] 21.4 15.8 34.9 20.5 RSm(LD / TD) 1.7 1.4 0.6 0.8 Ra(M)[μm] 1.4 1.3 0.7 1.4 Glossy surface Ra(G)[μm] 0.3 0.3 0.4 0.9 Ra(M / G) 4.7 4.3 1.8 1.6 Seal Strength Average [N / mm] 10.2 18.2 11.0 23.1 Coefficient of variation [-] 0.040 0.047 0.34 0.14 Glossiness 60.3 59.2 58.2 27.2

[0165] As is clear from Table 1, the water-soluble film of the present invention has excellent uniformity of sealing strength. By using the water-soluble film of the present invention for a package containing a medicine or the like, the obtained package has excellent uniformity of sealing strength, thereby being able to suppress the rupture of the package during storage or transportation. In addition, since the water-soluble films of Comparative Examples 1 and 2 do not have a convex shape on the film surface, the length of the convex shape and the like were not measured.

Claims

1. A water-soluble film comprising a polyvinyl alcohol resin, wherein: The ratio RSm (LD / TD) of the average length RSm (LD) of the roughness curve elements in the longitudinal direction of at least one film surface to the average length RSm (TD) of the roughness curve elements in the width direction is 1.2 or more and 2.5 or less, The film surface has a plurality of convex shapes having long sides in the longitudinal direction, The average aspect ratio of the convex shape is 2 or more and 10 or less, The average height of the convex shape is 0.5 μm or more and 5 μm or less, The convex shape has an average width of 10 μm to 50 μm, and an average length of 30 μm to 100 μm.

2. The water-soluble film according to claim 1, wherein The convex shape is a shape provided by transfer during molding.

3. The water-soluble film according to claim 1, wherein The convex shape is a shape provided by embossing.

4. The water-soluble film according to claim 1, wherein The ratio Ra (M / G) of the front-side to the back-side arithmetic mean roughness Ra of the film surface is 2 or more and 10 or less.

5. The water-soluble film according to claim 1, wherein The film surface having the RSm (LD / TD) of 1.2 or more and 2.5 or less is a matte surface.

6. A packaging body, wherein: A water-soluble film contains a drug, the water-soluble film contains a polyvinyl alcohol resin, and at the same time, in the water-soluble film, a ratio RSm (LD / TD) of an average length RSm (LD) of a roughness curve element in a longitudinal direction of a film surface on at least one side of the film to an average length RSm (TD) of a roughness curve element in a width direction is 1.2 or more and 2.5 or less, The film surface has a plurality of convex shapes having long sides in the longitudinal direction, The average aspect ratio of the convex shape is 2 or more and 10 or less, The average height of the convex shape is 0.5 μm or more and 5 μm or less, The convex shape has an average width of 10 μm to 50 μm, and an average length of 30 μm to 100 μm.

7. The packaging body according to claim 6, wherein: The convex shape is a shape provided by transfer during molding.

8. The packaging body according to claim 6, wherein: The convex shape is a shape provided by embossing.

9. The packaging body according to claim 6, wherein: The ratio Ra (M / G) of the front-side to the back-side arithmetic mean roughness Ra of the film surface is 2 or more and 10 or less.

10. The packaging body according to claim 6, wherein: The film surface having the RSm (LD / TD) of 1.2 or more and 2.5 or less is a matte surface.

11. The packaging body according to claim 6, wherein: The glossy side is the outer surface.

12. The package according to claim 6, wherein: The medicament is a pesticide, a detergent or a bactericide.

Citation Information

Patent Citations

  • Medicine package and method for producing medicine package

    JP2017110213A

  • Mold release film

    CN101678605A

  • Water-soluble film, medicine package, and manufacturing method of water-soluble film

    JP2017119434A